PENGARUH KURS DOLLAR, KEAMANAN, DAN KEBIJAKAN BEBAS VISA TERHADAP JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA KE BALI - Dalem, A.A. Gede Yudha Wisantika; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 2 (2021): VOL 10 NO 2, FEBRUARI 2021 [ 451 - 898], 2021)
T ourists visiting Bali makes economic grow in Indonesia. All assets owned by Bali archipelago must be optimized best as possible for advancement of tourism. The research objectives (1) analyze dollar exchange rate, security and visa-free policy simultaneously on the number of foreign tourist visits to Bali and (2) analyze dollar exchange rate, security and visa-free visit policies partially on the number of foreign tourists to Bali. D ata used are secondary data as 36 data with projections for the year 2011-2019 on a quarterly basis with the analysis method used is multiple linear regression analysis. The results show that simultaneously dollar exchange rate against the rupiah, security and visa-free policies affect number of foreign tourist visits to Bali. Partially it shows dollar exchange rate variable has significant positive effect on number of foreign tourist visits to Bali, visa-free visit policy variable has significant positive effect on number of foreign tourist visits to Bali, while security variable partially has no significant effect on number of foreign tourist visits to Bali. Together, these variables have an impact on changes in the quantity of foreign tourist visits to Bali.   Keywords: Number of visits, dollar exchange rate, security, visa-free policy.